Optimization of the measurement of residual stresses by the incremental hole drilling method. Part I: Numerical correction of experimental errors by a configurable numerical–experimental coupling - Ibrahim Mamane, A.S.; Giljean, S.; Pac, M.-J.; L’Hostis, G. (Composite structures, 2022)
The incremental hole drilling method is very effective in measuring the residual stress gradient in composite laminates. However, its reliability depends on the accuracy with which the calibration coefficients are determined. These coefficients are calculated using a finite element model. The samples’ features and the real experimental conditions must be taken into account in the simulation. Any mismatch can lead to inadequate calibration coefficients, thus introducing errors on residual stresses. Several calibration coefficients correction models exist for isotropic materials, but there is a lack of information on this subject concerning composite laminates. In this paper, the influence of three major experimental errors on the calibration coefficients is numerically investigated for composite laminates. The sensitivity of the coefficients to these errors is highlighted and a numerical correction method is proposed. [Display omitted] •Python program generates configurable finite element models of hole drilling method.•Models allow to study the influence of experimental errors on residual stresses.•Results highlight the sensitivity of the calibration coefficients to the errors.•Errors on increment depth are the most critical for composite laminates.•Correction of the calibration coefficients by a numerical–experimental coupling.